Studi Kasus Implementasi Rekam Medis Elektronik dengan Menggunakan Metode PIECES di Puskesmas Umbulharjo I Kota Yogyakarta - Pricilia Paruntu; Bangkit Ary Pratama; Rendi Ariyanto Sinanto (PT. Promosi Kesehatan Media, 2026)
Background: Community Health Centers (Puskesmas) play a crucial role in providing promotive, preventive, curative, and rehabilitative health services. To improve the efficiency and effectiveness of health management, the Umbulharjo I Community Health Center launched an Electronic Medical Record (EMR) system in April 2023. This study evaluates the system's implementation using the PIECES framework—which encompasses Performance, Information, Economics, Control, Efficiency, and Service—to identify strengths and areas for improvement. Methods: This study adopted a descriptive qualitative design. Data were collected through interviews, direct observation, and document review involving healthcare workers using the system, then analyzed across the six dimensions of the PIECES framework. Results and Discussion: Results indicate that the EMR generally improves service delivery and data management. The system is easy to operate and supports work efficiency, although its performance is highly dependent on stable internet connectivity. The information generated is relevant but not entirely accurate or complete, especially for population-based reports. Economically, the system reduces operational costs and administrative workload. However, limited supporting facilities—such as laptops, scanners, and electronic signature devices—remain a challenge. Security is maintained through user authentication and an internal network, but data backup is still performed manually. Although the EMR facilitates services, technical glitches and incomplete implementation in some units, including maternal and child health services, continue to pose challenges. Conclusion: The implementation of the EMR at Umbulharjo I Community Health Center has made a positive contribution to health management and service quality. However, improvements in infrastructure, user training, and system features are needed to achieve more effective and comprehensive use.